Användning av geografiskt informationssystem (GIS) vid studier av nötkreatur i landskapet - Aronsson, Peter (2008)
The Animal Protection Agency was in 2006, commissioned by the Government to: Evaluate how free range animals in the winter, can be kept and managed with special emphasis to animal welfare. The Animal Protection Agency was closed later in 2006 and the commission moved to the Swedish Board of Agriculture. The keeping of free range out wintered cattle, certain basic requirement are needed: by regulation, cattle should have access to a lying hall or other building that gives protection against aversive weather and wind and should offer a dry and clean lying area. There is a possibility for farmers that get an exemption from this regulation. But cases regarding farms which have had difficulties for this exemption has led to a discussion about if the animals can get the same protection in the nature which is comparable to a lying- hall. In a project, a group of researcher from Swedish University of Agricultural Sciences, should investigate how cattle uses the natural vegetation and landscape as protection for aversive weather and how lying areas are characterized. The aim with this work was to test the methodology that is intended to be used in the project. The approach covers production of map analysis through GIS (geographic information systems), position determination through GPS (global position system) and use of weather information to get a data set which could be used for a statistical analysis. In this study, data from an existing farm which normally out winters cattle, were used. Realistic landscape and vegetation conditions were thus used for the methology testing. A literature survey was also done on the topic and the equipment that can be used in the coming experiments was tested. The conclusion was that the methodology can be used in future studies, but some changes are also proposed for the future studies.